PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS WHO DO NOT MEET THE REQUIREMENTS - Sherimbetova, Zamira (International Journal of Psychosocial Rehabilitation, 2020)
In this research paper describes psychological characteristics of modern students as a condition for the formation of a future specialist. The paper reveals the psychological characteristics of modern students studying in universities who do not meet the requirements.Based on the information studied on the psychological characteristics of students in the process of writing the article, the need for an integrated approach to the formation of future specialists is revealed.